(untitled) (Research, Society and Development, 2025)
Objective: The present study aims to report a clinical case of a frontal bone fracture associated with a Le Fort II fracture, focusing on the clinical manifestations, as well as the therapeutic approach adopted. Methodology: This is a retrospective and descriptive observational study based on the analysis of the patient’s medical record, imaging exams, and photographic records, with authorization obtained through a Free and Informed Consent Form (FICF). Results: A female patient was admitted to the University Hospital of Western Paraná for trauma resulting from an automobile accident. Physical examination revealed an extensive laceration in the frontal region, associated with mild edema and local bone depression. Computed Tomography (CT) of the skull and face revealed fractures of the anterior and posterior walls of the frontal sinus, concomitant with a Le Fort II type fracture. Conclusion: Diagnosis is based on clinical evaluation complemented by imaging studies, with treatment defined according to the severity and type of injury, potentially ranging from conservative management to surgical intervention, such as reduction, fixation, obliteration, or cranialization. Surgical planning must be individualized, considering the anatomical compromise, associated fractures, and the balance between functional and aesthetic outcomes.